State of the Art in Quorum-Based Sleep/Wakeup Scheduling MAC Protocols for Ad Hoc and Wireless Sensor Networks. (8th February 2022) - Alzahrani, Eman; Bouabdallah, Fatma; Almisbahi, Hind
Abstract : In energy-constrained networks, designing an energy-efficient MAC protocol is crucial since the MAC protocol controls the access of the nodes to the shared wireless medium. Indeed, an efficient MAC protocol should reduce or even mitigate the consumption of the main sources of energy wastage, namely, overhearing, collision, and idle listening, and hence the network lifetime will be improved. One of the most efficient solutions is designing a MAC protocol that utilizes the quorum concept to increase energy efficiency by reducing idle listening and overhearing. Researchers have proposed several quorum-based MAC protocols to conserve energy. This paper presents a detailed overview and classification of several existing quorum-based sleep/wakeup scheduling MAC protocols. We classify these quorum-based MAC protocols into homogeneous and heterogeneous based on their quorum system characteristics. Moreover, we further classify these protocols according to the guaranteed intersection between any two quorums into fixed and limited. Furthermore, we compare these protocols in terms of their quorum system characteristics, limitations, and performance. Finally, a guide for future research directions is presented.